Iron sulfur cluster biogenesis in chloroplasts - Ye, Hong, author; Pilon-Smits, Elizabeth, advisor; Pilon, Marinus, advisor; Lapitan, Nora, committee member; Bush, Daniel R., committee member (Colorado State University. Libraries, 2005)
Iron-sulfur ([Fe-S]) clusters are essential cofactors for proteins involved in many essential processes. The plant chloroplast is known to have its own biosynthetic machinery for [Fe-S] clusters, but the components have long been unknown. Important processes that depend on this machinery include photosynthesis and nitrate- and sulfate assimilation. The goal of this thesis research was to discover some of the mechanisms and components of this machinery. CpNifS, a NifS-like cysteine desulfurase in chloroplasts, was the first identified component of the [Fe-S] biogenesis machinery in plastids. As described in this thesis, CpNifS was found to be required for chloroplast-mediated [Fe-S] assembly. The removal of CpNifS from chloroplast stroma led to a complete loss of [Fe-S] formation (see Chapter 2). CpSufE is a newly identified component of this machinery (Chapter 3). It activates cysteine desulfurase activity 40-fold and stimulates [Fe-S] formation 20-fold by forming a complex with CpNifS. CpIscA is a recently identified molecular scaffold in this machinery, modulating the formation of a [2Fe-2S] cluster and delivering it to ferredoxin (see Chapter 4). All three proteins AtCpNifS, AtCpSufE and AtCpIscA appear to be present in a ~600 kDa complex in vivo, tentatively named the plastidic [Fe-S] synthase complex in this thesis. These new and other published data were integrated to develop a working model for [Fe-S] cluster biogenesis in chloroplasts. Based on in vivo expression analyses and preliminary results from transgenic plants (see Chapter 5), implications of the [Fe-S] cluster biogenesis machinery in plastidic homeostasis of iron and sulfur and plant selenium metabolism are discussed.
Keywords: biochemistry; botany; molecular biology